Neonatal Sepsis: A Profile of a Changing Spectrum - Venkatnarayan, K; Bej, PK; Thapar, RK (Journal of Nepal Paediatric Society, 2015)
Introduction: The clinical features of neonatal sepsis are protean and are based on variety of clinical, demographic and laboratory profile of suspected cases. Objectives: To describe the aforementioned profiles in neonates presenting with clinically suspected sepsis based on pre-defined clinical criteria. Material and Methods: Design: Cross-Sectional Study; Setting: Level-2 NICU, Tertiary Care Hospital; Duration: Jan 2011 to Jul 2012. Subjects: 50 consecutive neonates presenting with any of the predefined clinical criteria were assessed for presence of maternal risk factors and studied with respect to: Gestational age, sepsis screen, clinical profile and antibiotic sensitivity of the organisms cultured. Results: Out of the fifty neonates, 38 (76%) were early onset sepsis. The sepsis screen showed an overall sensitivity of 73%, specificity of 54%; with a positive predictive value of 41% and a negative predictive value of 83%. The most common organism cultured was Staphylococcus aureus followed by E Coli, Pseudomonas, Coagulase Negative Staphylococcus and Group B Streptococcus. Ampicillin and Amikacin fared better than Cefotaxime and Gentamicin for Gram positive and Gram negative organisms, respectively. Overall, 37 babies responded to first line antibiotics and 11 required a change of antibiotics. One required addition of inotropes and two of the neonates died. Conclusion: A clinical diagnosis of sepsis based on predefined clinical criteria along with maternal risk factors, over- treated 27 babies (71%) with EONS and 8 babies (66.6%) with LONS. However, such a clinical diagnosis was supported by a septic screen almost twice as frequently (50% Vs 26.3%) in LONS. Staphylococcus aureus was the most common organism isolated. J Nepal Paediatr Soc 2014;34(3):207-214 DOI: http://dx.doi.org/10.3126/jnps.v34i3.11236